2021
DOI: 10.1111/anu.13333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary manganese supplementation on growth performance, antioxidant capacity, immune function and intestinal microbiota in Pacific white shrimp Litopenaeus vannamei

Abstract: Water manganese (Mn) is apparently insufficient to meet aquatic animals' metabolic requirement, and their food is considered as the major Mn source. Currently, researches reporting the effects of dietary Mn inclusion on physiological and metabolic function in Litopenaeus vannamei (L. vannamei) are very scarce. Therefore, 8-week feeding trail was conducted to determine dietary Mn requirement for L. vannamei and further evaluate the effects of dietary Mn supplementation on tissue Mn concentration, antioxidant en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…If external stress exceeds the body’s tolerance, then the cell eventually goes to the apoptotic pathway. Relevant research has been reported in fish [ 16 ], shrimp [ 17 , 18 ], and crabs [ 19 , 20 ] that the body responds to external environmental stresses by regulating its own immune system. Heat shock protein (HSP) are a highly conserved protein family that maintain cellular homeostasis and play an important role in the early stage of the low-temperature-tolerance mechanism in fish [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…If external stress exceeds the body’s tolerance, then the cell eventually goes to the apoptotic pathway. Relevant research has been reported in fish [ 16 ], shrimp [ 17 , 18 ], and crabs [ 19 , 20 ] that the body responds to external environmental stresses by regulating its own immune system. Heat shock protein (HSP) are a highly conserved protein family that maintain cellular homeostasis and play an important role in the early stage of the low-temperature-tolerance mechanism in fish [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%